A HAEMORRHAGIC DISORDER IN PREGNANCY DUE TO AN "ANTICOAGULANT" PREVENTING THE CONVERSION OF FIBRINOGEN TO FIBRIN. Issue 3 (May 1960) - Baker, S. J.; Jacob, E.
Abstract : A bleeding disorder occurring during labour and affecting mother and foetus is described. All stages of coagulation were normal until the reaction fibrinogen→fibrin. Either there was some abnormality present in the fibrinogen molecule, or there was an "anticoagulant" acting at this stage. The abnormality was reversible by protamine sulphate and toluidine blue, but in other respects did not resemble hyperheparinaemia. Reversibility of a clotting defect by protamine or toluidine blue is not sufficient evidence on which to make a diagnosis of hyperheparinaemia. Demonstration of a prolonged clotting time occurring in late pregnancy does not necessarily justify the diagnosis of "afibrinogenaemia."